KEPENTINGAN JEPANG MENGEMBANGKAN KERJASAMA DENGAN NEGARA ASIA TENGGARA DALAM ASEAN +3 - , Ingga Suwandana, Dra. Siti Khoiriati, MA ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Joint Declaration on the Comprehensive Economic is an economic agreement between Japan and ASEAN countries that allowed Japan to cooperate both bilaterally and multilaterally. Japan's initiative this agreement is taken as one of importance to developing cooperation in the economic field that is of interest to serve as a core country in the economic development of ASEAN countries. Japanese initiative is also based on rapid economic development are driving the need to make investments abroad. But with the development of Japanese investment abroad is increasing regional economic integration produces economies subordinated countries are smaller and weaker against the Japanese economy. Cooperation of Japan and ASEAN +3 countries is based on the dimensions of the economic order in which developing countries serve only to provide cheap labor for manufacturing industry, basic materials for industries and commodities. Based on this it can be said that Japan's attempt to create an exclusive market.